INTERNAL SERVICE QUALITY PADA SMA DI KECAMATAN RONGKOP DAN KARANGMOJO KABUPATEN GUNUNGKIDUL - Rinto Bayu Wibowo (Ideguru: Jurnal Karya Ilmiah Guru, 2017)
SERVQUAL model developed by Parasuraman, Zeitaml & Berry (1985) has been widely used to measure external customer satisfaction, but the models to measure internal customer satisfaction in the field of education in Indonesia is still rarely done, so in this study the internal customer satisfaction measurement will be done using ISQ models (Internal Service Quality) in the field of educational services. This study aims to assess the internal customer perceptions of a high school internal quality services with ISQ models in the district Rongkop and Karangmojo, this study also aims to identify differences in perceptions of internal customers in the education services with ISQ dimensions (reliability, responsivenes, assurance, empathy and tangible,) based on personal characteristics (highschool status, profession, job tenure, and gender) as schools demographics in the Rongkop and Karangmojo district. This type of research is descriptive quantitative research methods, data collection using 22 ISQ item questionnaire, survey instruments were adopted based on SERVQUAL dimensions (reliability, responsiveness, assurance, empathy and tangible). The results showed that perceptions of internal customers in SMA 1 Rongkop, SMA Muhammadiyah Rongkop, SMA 1 Karangmojo and SMA Pembangunan Karangmojo achieve the lowest mean score on the dimensions of reliability (4.01), whereas the highest scores on the dimensions of assurance (4,19). There is no statistically significant difference in the perception of reliability dimension with all personal characteristics. There is a statistically significant difference in the perception of responsive dimension with the work period personal characteristics. The internal customer perception of assurance dimension have a significantly differences with high school status personal characteristics. There is statistically significant differences in the perceptions of empathy dimensions on personal characteristics job tenure while the other personal characteristics doesn’t make any difference. In the tangible dimension, there is statistically different perceptions of internal customers on personal characteristics of respondents profession, but there was no difference for the other personal characteristics in this dimension.